A UV photodetector based on amorphous In-doped Ga2O3 nanomaterial and its preparation method

By using amorphous In-doped Ga2O3 nanomaterial as the photosensitive layer, the problem of insufficient photocurrent of existing ultraviolet photodetectors is solved, and a higher signal-to-noise ratio and detection sensitivity are achieved, expanding its application areas.

CN115274906BActive Publication Date: 2025-03-07JILIN UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202210903894.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-07-29
Publication Date
2025-03-07
Estimated Expiration
2042-07-29

AI Technical Summary

Technical Problem

The existing ultraviolet photoelectric detectors have low photocurrent, resulting in insufficient signal-to-noise ratio and detection sensitivity, limiting their application in military, environmental, medical and other fields.

Method used

An amorphous In-doped Ga2O3 nanomaterial is used as the photosensitive layer, and an In-doped Ga2O3 nanomaterial photosensitive layer and Au metal interdigital electrode are prepared on a quartz substrate to form an efficient ultraviolet photodetector.

Benefits of technology

It significantly improves the photocurrent of the ultraviolet photodetector, enhances the signal-to-noise ratio and detection sensitivity, and gives the device a broader application prospect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115274906B_ABST
    Figure CN115274906B_ABST
Patent Text Reader

Abstract

A UV photodetector based on amorphous In-doped Ga2O3 nanomaterials and a preparation method thereof belong to the field of UV photodetection technology. The UV photodetector is composed of a quartz substrate, an amorphous In-doped Ga2O3 nanomaterial photosensitive layer and an Au metal interdigital electrode. First, the quartz substrate is cleaned and dried, and then gallium nitrate nine hydrate, indium nitrate four hydrate, polyoxyethylene lauryl ether and citric acid are added to deionized water to obtain an In-doped Ga2O3 precursor solution; then the precursor solution is spin-coated on the quartz substrate, and after drying, substrate cooling and sintering, an amorphous In-doped Ga2O3 nanomaterial photosensitive layer is obtained; finally, after photolithography and magnetron sputtering, an Au metal interdigital electrode is obtained on the photosensitive layer; thus, a UV photodetector based on amorphous In-doped Ga2O3 nanomaterials with simple process, few steps, low cost and high response to UV light is prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of ultraviolet photoelectric detection technology, and specifically relates to a method based on amorphous In doped Ga 2 O 3 Ultraviolet photodetector of nanomaterials and preparation method thereof. Background Art

[0002] Ultraviolet light is an electromagnetic wave with a wavelength of 10nm-400nm, which is mainly divided into the following bands: visible-blind is about 300-400nm, solar-blind is 200-280nm, and vacuum ultraviolet (VUV) is 10-200nm. The ultraviolet photoelectric detector is a detector that converts ultraviolet light into electrical signals. Its working principle is based on the external photoelectric effect, which refers to the phenomenon that when the electrons in the photosensitive layer of the detector absorb the energy of photons and make transitions under the irradiation of electromagnetic waves with a frequency higher than a certain frequency, a current is formed under the action of the electric field.

[0003] High-performance UV detectors are widely used in military, environmental, medical and other fields. They can be used for UV intensity detection, optical communication, missile tail flame detection, fire detection, etc. With the continuous advancement of semiconductor materials and device preparation processes, wide bandgap semiconductor UV detectors have become a hot topic in the field of UV detection technology. Wide bandgap materials do not absorb visible light themselves, which can effectively make up for the disadvantage that narrow bandgap semiconductor UV detectors based on Si, GaAs, etc. need to work with filtering equipment; and there are many types of wide bandgap materials, stable properties, diverse preparation methods and low cost, which have important practical value. However, some inherent deficiencies of wide bandgap materials, such as low carrier mobility, short exciton lifetime, and many traps and defects in oxide materials, lead to problems such as low device photocurrent and low responsivity.

[0004] With the development of science and technology, the requirements for the performance parameters of ultraviolet photodetectors in various application fields are constantly increasing, including higher photocurrent, lower dark current and faster response / recovery speed, etc. Among them, improving the photocurrent of the device is extremely important, which can help improve the signal-to-noise ratio and detection sensitivity of the device, increase the upper limit of light intensity detection, and make the device have a broader application prospect. Summary of the invention

[0005] The purpose of the present invention is to provide a method based on amorphous In doped Ga 2 O 3 A nanomaterial ultraviolet photodetector and a preparation method thereof. The method is simple and easy to implement, has few steps, low cost, low equipment requirements, has a high response to ultraviolet light, is suitable for mass production, and has important application value.

[0006] In order to achieve the above object, the technical solution of the present invention is:

[0007] A novel method based on amorphous In-doped Ga 2 O 3 The ultraviolet photodetector made of nanomaterials consists of a quartz substrate, an amorphous In-doped Ga 2 O 3 It consists of a nanomaterial photosensitive layer and Au metal interdigital electrodes.

[0008] As an improvement to the above technical solution, amorphous In doped Ga 2 O 3 The thickness of the nanomaterial photosensitive layer is 300-400nm.

[0009] As an improvement to the above technical solution, the electrode length, electrode spacing, electrode width and electrode thickness of the Au metal interdigital electrode are 0.8-1.2 mm, 10-30 μm, 10-30 μm and 100-150 nm respectively.

[0010] The present invention discloses a method based on amorphous In doped Ga 2 O 3 The preparation method of the ultraviolet photodetector of nanomaterials comprises the following steps:

[0011] (1) Cleaning the substrate

[0012] The quartz substrate was ultrasonically cleaned in acetone, ethanol and deionized water for 10 to 20 minutes respectively, and then dried;

[0013] (2) Preparation of amorphous In-doped Ga 2 O 3 Nanomaterial photosensitive layer

[0014] First, prepare In-doped Ga 2 O 3 Precursor solution: Add 4.41-6.30 g of gallium nitrate nine hydrate, 0.56-1.68 g of indium nitrate tetrahydrate, 20-40 μL of polyoxyethylene lauryl ether, and 0.020-0.044 g of citric acid to 20-40 mL of deionized water, stir in a water bath at 70-80 ° C for 20-40 minutes, and finally place the solution in a dark place for 18-30 hours to obtain In-doped Ga 2 O 3 Precursor solution;

[0015] In-doped GaN is prepared on the surface of the quartz substrate dried in step (1). 2 O 3 Nanomaterial photosensitive layer: In-doped Ga was spin-coated on the surface of a dried quartz substrate 2 O3 The precursor solution is spin-coated to form a thin film at a speed of 2500 to 3500 rpm for 25 to 35 seconds; the substrate is dried at 90 to 110°C for 8 to 12 minutes and then cooled to room temperature; the spin coating, drying and substrate cooling steps are repeated 7 to 13 times, and finally the In-doped Ga 2 O 3 The nanofilm and the quartz substrate are sintered at 650-750°C for 20-40 minutes to obtain In-doped Ga on the surface of the quartz substrate. 2 O 3 Nanomaterial photosensitive layer, thickness is 300-400nm;

[0016] (3) Preparation of Au metal interdigital electrodes

[0017] The main processes include spin coating of photoresist, photolithography of interdigital patterns, development and sputtering steps;

[0018] First, in the In-doped Ga 2 O 3 A positive photoresist film with a thickness of 0.5 to 1 μm is spin-coated on the surface of the nanomaterial photosensitive layer, the spin-coating speed is 800 to 1500 rpm, the spin-coating time is 20 to 30 seconds, and then pre-baking is performed at a temperature of 80 to 100° C. for 10 to 20 minutes; then, a photolithography mask plate complementary to the Au metal interdigital electrode structure to be prepared is placed on the photoresist film, ultraviolet exposure is performed for 60 to 90 seconds, and the exposed photoresist is removed after 30 to 40 seconds of development; finally, a post-baking treatment is performed at 100 to 120° C. for 10 to 20 minutes to obtain a photoresist film with hollow interdigital windows;

[0019] Au metal interdigital electrodes were prepared by magnetron sputtering technology with a vacuum degree of 4.0×10 -3 ~8.0×10 -3 Pa, the flow rate of argon gas is 20-30 sccm; then the pressure of the vacuum chamber is adjusted to 1-3 Pa, bias voltage is applied, the sputtering power is 60-120 W, and the sputtering time is 10-15 minutes; after the sputtering is completed, Au metal interdigital electrodes are obtained in the hollow interdigital windows, and then the substrate is placed in acetone for ultrasonication for 10-30 seconds, the unexposed photoresist and the Au layer thereon are peeled off, the acetone is washed off and blown dry, and the amorphous In-doped Ga-based substrate of the present invention is prepared. 2 O 3 Ultraviolet photodetectors based on nanomaterials.

[0020] As an improvement to the above technical solution, in step (2), the polyoxyethylene lauryl ether is L23 polyoxyethylene lauryl ether.

[0021] As an improvement to the above technical solution, in step (2), the citric acid is citric acid monohydrate. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0023] Figure 1 : A schematic diagram of the structure of the ultraviolet photodetector prepared by the present invention;

[0024] Figure 2 : In-doped Ga in Examples 1, 2, 3 and 4 of the present invention 2 O 3 XRD pattern of the photosensitive layer of the nanomaterial;

[0025] Figure 3 : In-doped Ga in Examples 1, 2, 3 and 4 of the present invention 2 O 3 UV-visible absorption graph of the photosensitive layer of the nanomaterial;

[0026] Figure 4 : Current-voltage characteristic curve of the device prepared in Example 1 of the present invention (In doping concentration is 0%);

[0027] Figure 5 : Current-voltage characteristic curve of the device prepared in Example 2 of the present invention (In doping concentration is 10%);

[0028] Figure 6 : Current-voltage characteristic curve of the device prepared in Example 3 of the present invention (In doping concentration is 20%);

[0029] Figure 7 : Current-voltage characteristic curve of the device prepared in Example 4 of the present invention (In doping concentration is 30%).

[0030] like Figure 1 As shown, the ultraviolet photodetector of the present invention comprises, from bottom to top, a quartz substrate 1, an amorphous In-doped Ga 2 O 3 The In-doped Ga 2 O 3The nano material photosensitive layer 2 is amorphous and has a thickness of about 300-400 nm. The electrode length, electrode spacing, electrode width and electrode thickness of the Au metal interdigital electrode 3 are 0.8-1.2 mm, 10-30 μm, 10-30 μm and 100-150 nm respectively.

[0031] like Figure 2 As shown, it shows that after In doping, Ga 2 O 3 The nanomaterial photosensitive layer changes from the crystalline state of Example 1 to the amorphous state of Examples 2, 3, and 4.

[0032] like Figure 3 As shown, it is shown that Ga of Example 1 of the present invention 2 O 3 The bandgap width of the nanomaterial photosensitive layer is 4.84 eV; In doped Ga 2 O 3 The bandgap widths of the nanomaterial photosensitive layer are 4.46eV, 4.28eV, and 4.18eV respectively.

[0033] like Figure 4 As shown, when the In doping concentration in the device is 0%, under a bias of 5V, the photocurrent of the device is 0.2nA, the dark current is 0.05nA, and the light-to-dark current ratio is 4.

[0034] like Figure 5 As shown, when the In doping concentration in the device is 10%, under a bias of 5 V, the photocurrent of the device is 32.2 nA, the dark current is 0.1 nA, and the light-to-dark current ratio is 322.

[0035] like Figure 6 As shown, when the In doping concentration in the device is 20%, under a bias of 5V, the photocurrent of the device is 2.65μA, the dark current is 1nA, and the light-to-dark current ratio is 2650.

[0036] like Figure 7 As shown, when the In doping concentration in the device is 30%, under a bias of 5 V, the photocurrent of the device is 409.54 μA, the dark current is 3 μA, and the light-to-dark current ratio is 136.51.

[0037] As can be seen from the above figure, the ultraviolet photodetector of the present invention adopts amorphous In doped Ga 2 O 3 Nanomaterials are used as light-sensitive layers. Since In and Ga are both group V elements, they are adjacent to each other in the original periodic table, and doping restrictions are relaxed, so Ga is allowed to 2 O 3The In element in GaO has a high doping ratio. First, the traditional crystalline substitutional doping has a low activation efficiency of the elements on the lattice, which limits the increase of the photocurrent, while doping in an amorphous state allows for a larger photocurrent. 2 O 3 As an amorphous material, the nanomaterial itself has high element activation efficiency, strong light absorption ability, high light utilization rate, and high photoelectric conversion efficiency. Finally, the resistance of the indium oxide film made with the same molar amount is small, while the resistance of the gallium oxide film is large. Therefore, the use of In to Ga 2 O 3 Heavy doping of nanomaterials can increase the photocurrent. Therefore, In can be used to dope Ga 2 O 3 Nanomaterials are transformed into an amorphous state, and the higher the doping amount of In element, the greater the photocurrent of the device, so the photocurrent of the ultraviolet photodetector can be greatly improved. In addition, from the ultraviolet visible absorption graph, it can be seen that the shift of the bandgap width of the detector's photosensitive layer is small, which can effectively detect ultraviolet rays.

[0038] At the same time, the process of the invention is simple, the ultraviolet photodetector prepared is small in size, suitable for mass production, and thus has important application value. The preparation method of the invention has the characteristics of simple preparation method, low cost, high light response, and promising large-scale production, and has good detection performance for ultraviolet light. DETAILED DESCRIPTION

[0039] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work, any modifications, equivalent substitutions, improvements, etc., should be included in the protection scope of the present invention.

[0040] Preparation Example 1:

[0041] A quartz substrate with a size of 15 mm×15 mm×1 mm was placed in acetone, ethanol and deionized water in turn for ultrasonic cleaning for 10 minutes and then dried.

[0042] Preparation of In-doped Ga on quartz substrate by sol-gel method 2 O 3 Nanofilm. First, prepare Ga without In doping 2 O 3Precursor solution: Add 6.30 g of gallium nitrate nonahydrate, 30 μL of L23 polyoxyethylene lauryl ether, and 0.032 g of citric acid monohydrate to 30 mL of deionized water, stir in a 75 °C water bath for 30 minutes, and finally place the solution in a dark place for 24 hours to obtain In-free Ga 2 O 3 Precursor solution; In-free GaN is spin-coated on the surface of the quartz substrate by spin coating. 2 O 3 The precursor solution was spin-coated at a speed of 3000 rpm for 30 seconds, and then dried at 100°C for 10 minutes. After the substrate was cooled to room temperature, the spin coating and drying steps were repeated 10 times. Finally, the In-free Ga 2 O 3 The film and the quartz substrate were sintered at 700°C for 30 minutes to obtain In-free GaN on the surface of the quartz substrate. 2 O 3 Nanofilm, thickness 350nm;

[0043] The Au metal interdigital electrode is prepared by spin coating photoresist, photolithography interdigital patterning, development and sputtering. 2 O 3 A layer of positive photoresist film (BP212-37S UV positive photoresist) with a thickness of 0.8 μm was spin-coated on the surface of the film at a spin-coating speed of 1200 rpm for 20 seconds, and then pre-baked at 80°C for 15 minutes; then, a photolithography mask plate complementary to the interdigital electrode structure to be prepared was placed on the photoresist, UV-exposed for 80 seconds, and the exposed photoresist was removed after 30 seconds of development; finally, after a post-baking treatment at 120°C for 15 minutes, a photoresist film with hollow interdigital windows was obtained; Au metal interdigital electrodes were prepared by magnetron sputtering technology, and the vacuum degree was 6×10 -3 Pa, the flow rate of argon gas is 25 sccm; then the pressure of the vacuum chamber is adjusted to 1.5 Pa, bias voltage is applied, the sputtering power is 90 W, and the sputtering time is 12 minutes.

[0044] Based on In-free Ga 2 O 3 Preparation of ultraviolet photodetectors made of nanomaterials. After sputtering, Au metal interdigital electrodes are obtained in the hollow interdigital windows, and the substrate is then placed in acetone for 15 seconds for ultrasonic treatment. The unexposed photoresist and the Au layer thereon are peeled off, the acetone is washed off and the device is dried, and the device is completed.

[0045] Preparation Example 2:

[0046] A quartz substrate with a size of 15 mm×15 mm×1 mm was placed in acetone, ethanol and deionized water in turn for ultrasonic cleaning for 10 minutes and then dried.

[0047] Preparation of In-doped Ga on quartz substrate by sol-gel method 2 O 3 Nanofilm. First, prepare In-doped Ga 2 O 3 Precursor solution: Add 5.67 g of gallium nitrate nine hydrate, 0.56 g of indium nitrate tetrahydrate, 30 μL of L23 polyoxyethylene lauryl ether, and 0.032 g of citric acid monohydrate to 30 mL of deionized water, stir in a 75 °C water bath for 30 minutes, and finally place the solution in a dark place for 24 hours to obtain In-doped Ga 2 O 3 Precursor solution; In-doped Ga is spin-coated on the surface of the quartz substrate by spin coating 2 O 3 The precursor solution was spin-coated at a speed of 3000 rpm for 30 seconds, and then dried at 100°C for 10 minutes. After the substrate was cooled to room temperature, the spin coating and drying steps were repeated 10 times. Finally, the In-doped Ga 2 O 3 The film and the quartz substrate were sintered at 700°C for 30 minutes to obtain In-doped Ga on the surface of the quartz substrate. 2 O 3 Nanofilm, thickness 350nm;

[0048] The Au metal interdigital electrodes were prepared by spin coating photoresist, photolithography of interdigital patterns, development and sputtering. The specific implementation was the same as in Example 1.

[0049] Based on amorphous In doped Ga 2 O 3 Preparation of ultraviolet photodetector made of nanomaterials. The specific implementation is the same as Example 1.

[0050] Preparation Example 3:

[0051] A quartz substrate with a size of 15 mm×15 mm×1 mm was placed in acetone, ethanol and deionized water in turn for ultrasonic cleaning for 10 minutes and then dried.

[0052] Preparation of In-doped Ga on quartz substrate by sol-gel method 2 O 3 Nanofilm. First, prepare In-doped Ga 2 O 3Precursor solution: Add 5.04 g of gallium nitrate nine hydrate, 1.12 g of indium nitrate tetrahydrate, 30 μL of L23 polyoxyethylene lauryl ether, and 0.032 g of citric acid monohydrate to 30 mL of deionized water, stir in a 75 °C water bath for 30 minutes, and finally place the solution in a dark place for 24 hours to obtain In-doped Ga 2 O 3 Precursor solution; In-doped Ga is spin-coated on the surface of the quartz substrate by spin coating 2 O 3 The precursor solution was spin-coated at a speed of 3000 rpm for 30 seconds, and then dried at 100°C for 10 minutes. After the substrate was cooled to room temperature, the spin coating and drying steps were repeated 10 times. Finally, the In-doped Ga 2 O 3 The film and the quartz substrate were sintered at 700°C for 30 minutes to obtain In-doped Ga on the surface of the quartz substrate. 2 O 3 Nanofilm, thickness 350nm;

[0053] The Au metal interdigital electrodes were prepared by spin coating photoresist, photolithography of interdigital patterns, development and sputtering. The specific implementation was the same as in Example 1.

[0054] Based on amorphous In doped Ga 2 O 3 Preparation of ultraviolet photodetector made of nanomaterials. The specific implementation is the same as Example 1.

[0055] Preparation Example 4:

[0056] A quartz substrate with a size of 15 mm×15 mm×1 mm was placed in acetone, ethanol and deionized water in turn for ultrasonic cleaning for 10 minutes and then dried.

[0057] Preparation of In-doped Ga on quartz substrate by sol-gel method 2 O 3 Nanofilm. First, prepare In-doped Ga 2 O 3 Precursor solution: 4.41 g of gallium nitrate nine hydrate, 1.68 g of indium nitrate tetrahydrate, 30 μL of L23 polyoxyethylene lauryl ether, and 0.032 g of citric acid monohydrate were added to 30 mL of deionized water, stirred in a water bath at 75 °C for 30 minutes, and finally the solution was placed in a dark place for 24 hours to obtain In-doped Ga 2 O 3 Precursor solution; In-doped Ga is spin-coated on the surface of the quartz substrate by spin coating 2 O 3The precursor solution was spin-coated at a speed of 3000 rpm for 30 seconds, and then dried at 100°C for 10 minutes. After the substrate was cooled to room temperature, the spin coating and drying steps were repeated 10 times. Finally, the In-doped Ga 2 O 3 The film and the quartz substrate were sintered at 700°C for 30 minutes to obtain In-doped Ga on the surface of the quartz substrate. 2 O 3 Nanofilm, thickness 350nm;

[0058] The Au metal interdigital electrodes were prepared by spin coating photoresist, photolithography of interdigital patterns, development and sputtering. The specific implementation was the same as in Example 1.

[0059] Based on amorphous In doped Ga 2 O 3 Preparation of ultraviolet photodetector made of nanomaterials. The specific implementation is the same as Example 1.

[0060] The above-described contents are only specific implementation modes of the present invention and cannot be used to limit the scope of implementation of the present invention. All equivalent changes and improvements made according to the scope of the patent application of the present invention should still fall within the scope covered by the patent of the present invention.

Claims

1. A method for preparing an ultraviolet photodetector based on amorphous In-doped Ga2O3 nanomaterial, the steps of which are as follows: (1) Cleaning the substrate The quartz substrate was ultrasonically cleaned in acetone, ethanol and deionized water for 10 to 20 minutes respectively, and then dried; (2) Preparation of amorphous In-doped Ga2O3 nanomaterial photosensitive layer First, prepare an In-doped Ga2O3 precursor solution: add 4.41-6.30 g of gallium nitrate nine hydrate, 0.56-1.68 g of indium nitrate tetrahydrate, 20-40 μL of polyoxyethylene lauryl ether, and 0.020-0.044 g of citric acid to 20-40 mL of deionized water, stir in a water bath at 70-80° C. for 20-40 minutes, and finally place the solution in a dark place and let it stand for 18-30 hours to obtain an In-doped Ga2O3 precursor solution; In step (1), a Ga2O3 nanomaterial photosensitive layer doped with In is prepared on the surface of the dried quartz substrate: a Ga2O3 precursor solution doped with In is spin-coated on the surface of the dried quartz substrate to form a thin film, the spin-coating speed is 2500-3500 rpm, and the spin-coating time is 25-35 seconds; the substrate is dried at 90-110° C. for 8-12 minutes and then cooled to room temperature; the spin-coating, drying, and substrate cooling steps are repeated 7-13 times, and finally the Ga2O3 nanofilm doped with In is sintered together with the quartz substrate at 650-750° C. for 20-40 minutes, thereby obtaining a Ga2O3 nanomaterial photosensitive layer doped with In on the surface of the quartz substrate; (3) Preparation of Au metal interdigital electrodes The photosensitive layer of the In-doped Ga2O3 nanomaterial is subjected to spin coating of photoresist, photolithography of interdigital patterns, development and sputtering to prepare Au metal interdigital electrodes, thereby obtaining the ultraviolet photodetector based on the amorphous In-doped Ga2O3 nanomaterial.

2. The method for preparing an ultraviolet photodetector based on amorphous In-doped Ga2O3 nanomaterial according to claim 1, characterized in that: Step (3) Spin-coating photoresist, photolithography interdigital pattern, development and sputtering is to spin-coat a positive photoresist film with a thickness of 0.5 to 1 μm on the surface of the In-doped Ga2O3 nanomaterial photosensitive layer, with a spin-coating speed of 800 to 1500 rpm and a spin-coating time of 20 to 30 seconds, and then pre-bake at 80 to 100° C. for 10 to 20 minutes; then, place a photolithography mask plate complementary to the Au metal interdigital electrode structure to be prepared on the photoresist film, expose to ultraviolet light for 60 to 90 seconds, and remove the exposed photoresist after 30 to 40 seconds of development; finally, after a post-bake treatment at 100 to 120° C. for 10 to 20 minutes, a photoresist film with hollow interdigital windows is obtained; then, the Au metal interdigital electrode is prepared by magnetron sputtering technology, and the vacuum degree is 4.0×10 -3 ~8.0×10 -3 Pa, the flow rate of argon gas is 20-30 sccm; then the pressure of the vacuum chamber is adjusted to 1-3 Pa, bias voltage is applied, the sputtering power is 60-120 W, and the sputtering time is 10-15 minutes; after the sputtering is completed, Au metal interdigital electrodes are obtained in the hollow interdigital windows, and then the substrate is placed in acetone for ultrasonication for 10-30 seconds, the unexposed photoresist together with the Au layer thereon is peeled off, the acetone is washed off and blown dry, and Au metal interdigital electrodes are obtained on the In-doped Ga2O3 nanomaterial photosensitive layer.

3. The method for preparing an ultraviolet photodetector based on amorphous In-doped Ga2O3 nanomaterial according to claim 1, characterized in that: The thickness of the amorphous In-doped Ga2O3 nanomaterial photosensitive layer is 300-400nm.

4. The method for preparing an ultraviolet photodetector based on amorphous In-doped Ga2O3 nanomaterial according to claim 1, characterized in that: The electrode length, electrode spacing, electrode width and electrode thickness of the Au metal interdigital electrode are 0.8-1.2 mm, 10-30 μm, 10-30 μm and 100-150 nm respectively.

5. The method for preparing an ultraviolet photodetector based on amorphous In-doped Ga2O3 nanomaterial according to claim 1, characterized in that: The polyoxyethylene lauryl ether is L23 polyoxyethylene lauryl ether, and the citric acid is citric acid monohydrate.

6. An ultraviolet photodetector based on amorphous In-doped Ga2O3 nanomaterials, characterized in that: The method is prepared by any one of claims 1 to 5.